Fixes that Fit: Systems Thinking in Academic Integrity - Vogt, Lisa; Scurr, Cory (Canadian Perspectives on Academic Integrity, 2023)
Academic misconduct is typically recorded on student files to deter cheating and identify repeat offenders, but how often is this data analyzed to find systemic issues? By collecting student data, Prinsloo and Slade (2017) assert that higher education has a duty to act in creating improved student experiences. Teymouri et al. (2022) propose the use of academic misconduct data to identify gaps in student supports, policy education, and assessment design. This session will apply a systems thinking approach to propose that post-secondary institutions can create institutional responses in support of academic integrity based on findings from collected academic misconduct data. Reallocating the intensive energy required to respond to misconduct toward early education and assessment design benefits both staff and students. Literature supporting a systems thinking approach for effective data use will be discussed, as well as examples from practice at Conestoga College. Attendees will gain frameworks for applying systems thinking and ethical data use, as well as the opportunity for questions and further discussion.